Horner Syndrome in Neurofibromatosis Type 1. Issue 1 (January 2015) - Lee, Jang Hyun; Jeen, Yoon-Mi; Kang, Sang Gue; Tark, Min Seung; Kim, Chul Han
<x xml:space="preserve">Abstract</x> Abstract The authors report a rare case of Horner syndrome in a patient with neurofibromatosis type 1 (NF-1). A 31-year-old man visited the clinic with drooping left eyelid. The physical examination revealed ptosis of the left eyelid, miotic pupil, facial anhidrosis, and several skin masses on the chest. The radiological examination of the chest demonstrated a well-defined left posterior mediastinal mass close to the vertebral bodies of the upper thoracic spine at the level of T1-T5. The masses of mediastinum and skin were totally removed. They were diagnosed as neurofibromas. Neurofibromatosis type 1 was diagnosed. To the best of my knowledge, this is a rare case of a patient with NF-1 who presented with Horner syndrome. Clinicians should be vigilant on the possibility of Horner syndrome in patients with NF-1.